Sports Leagues Scheduling Models, Combinatorial Properties, and Optimization Algorithms - Briskorn, Dirk (Lecture Notes in Economics and Mathematical Systems, 2008)
In the context of sports leagues scheduling (SLS) several groups' interests must be taken into account. This book treats requirements for sport leagues schedules to be realizable from an operational and a security point of view, attractive for spectators and tv channels, and fair for the conampeting teams. Formal problem definitions as well as integer programming models are presented and analyzed. Additionally, several fairness concepts are developed and their operability is investigated by means of graph theory. Moreover, this book presents algorithmic concepts that can be drawn upon to construct suitable schedules. This volume provides a deep understanding of problems arising in the context of SLS as well as approaches for dealing with these problems, being relevant for both theoreticians and practitioners.